Electrochemical Processes Coupled to a Biological Treatment for the Removal of Iodinated X-ray Contrast Media Compounds - Zhang, Wei; Soutrel, Isabelle; Amrane, Abdeltif; Fourcade, Florence; Geneste, Florence (Frontiers in Chemistry, 2020)
Iodinated X-ray contrast media (ICM) compounds are a form of intravenous radiocontrast containing iodine, which are rapidly eliminated via urine or faeces. The issue with the accumulation of ICM has received considerable critical attention since they are ubiquitously distributed in municipal wastewater effluents and in the aquatic environment and are not significantly eliminated by most biological sewage treatment processes. Among the methods that have been tested to eliminate ICM, electrochemical methods have significant advantages, since they can selectively cut the carbon-iodine bonds that are suspected to decrease their biodegradability. On the production sites, the recovery of iodine ions due to the carbon-iodine cleavage can be envisaged, which is particularly interesting to reduce the cost of the ICM production process. The coupling of an electrochemical process and a biological treatment can be carried out to mineralize the organic part of the formed by-products, allowing the recovery of the iodide ions. Therefore, the degradation of diatrizoate, a typical ionic ICM compound, by an electrochemical process was the purpose of this study. The electrochemical reduction of diatrizoate was performed using a flow cell with a graphite felt electrode at different potentials. The removal yield of diatrizoate reached approximately 100% in 2 hours and the main product, 3,5-diacetamidobenzoic acid, was quantitatively formed, showing that diatrizoate was almost completely deiodinated. According to the BOD5/COD ratio, the biodegradability of diatrizoate after electrolysis was considerably improved. Cyclic voltammetry analysis of the electroreduced solution showed several oxidation peaks. The electrochemical oxidation of the by-products formed after the first treatment by electroreduction was then performed at three different potentials to study the influence of electrochemical oxidation on biodegradability. Results showed that the degradation yield of the deiodinated by-products increased with the potential and reached 100 % at 1.3 V/SCE. Four different biological treatments were implemented during 21 days in stirred flasks with fresh activated sludge. The evolution of the mineralization during the biological treatment highlighted the biorecalcitrance of diatrizoate as previously estimated by the BOD5/COD ratio. Interestingly, the mineralization yield increased from 41% to 60% when electrochemical oxidation at 1.3 V/SCE was implemented after electroreduction.